2014
DOI: 10.1007/s40069-013-0061-0
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Effects of Carbon-Glass FRP Sheets in Combination with or without Concrete Beams

Abstract: The use of carbon fibers (CF) and glass fibers (GF) were combined to strengthen concrete flexural members. In this study, data of tensile tests of 94 hybrid carbon-glass FRP sheets and 47 carbon and GF rovings or sheets were thoroughly investigated in terms of tensile behavior. Based on comparisons between the rule of mixtures and test data, positive hybrid effects were identified for various (GF/CF) ratios. Unlike the rule of mixtures, the hybrid sheets with relatively low (GF/CF) ratios also produced pseudo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 11 publications
1
9
0
1
Order By: Relevance
“…On the other hand, Cross Ply 1 and Cross Ply 4 recorded tensile modulus which is consistent with the theoretical rule of mixture. The same phenomena apply to Cross-Ply 3 and Cross Ply 2, where both depicted quite close value of tensile strength and their tensile modulus also observed to follow the rule of mixture [19]. journal.ump.edu.my/ijame ◄…”
Section: Tensile Behaviour Of Hybrid Composite Balanced Cross-ply Andsupporting
confidence: 63%
“…On the other hand, Cross Ply 1 and Cross Ply 4 recorded tensile modulus which is consistent with the theoretical rule of mixture. The same phenomena apply to Cross-Ply 3 and Cross Ply 2, where both depicted quite close value of tensile strength and their tensile modulus also observed to follow the rule of mixture [19]. journal.ump.edu.my/ijame ◄…”
Section: Tensile Behaviour Of Hybrid Composite Balanced Cross-ply Andsupporting
confidence: 63%
“…In civil engineering context there are already several examples of applying the hybrid composite concept, mainly in the research and development of three main systems: (i) reinforcing bars for reinforced concrete (RC) structures [30][31][32][33][34][35][36][37]; (ii) externally bonded strengthening for RC structures [17,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], and (iii) pultruded profiles for new structures [53][54][55]. In a general way, experimental results have shown that a significant ductile response, similar or even better, than that of a steel-reinforced concrete member can be achieved with hybrid composites [31,36].…”
Section: Introductionmentioning
confidence: 99%
“…Externally bonded carbon fiber-reinforced polymer (CFRP) sheets have been widely used to restore or increase the capacities of reinforced concrete (RC) beams due to their advantages including their low weight, high strength and stiffness, high durability, and ease of application (Kang et al 2012;Ouezdou et al 2009;Grelle and Sneed 2013;Ren et al 2015). Many studies have been conducted to study the effect of CFRP sheets on the performance of RC beams (Al-Rousan and Issa 2011;Oudah and El-Hacha 2013a, b;EISafty et al 2014;Kang et al 2014). However, several researchers have demonstrated that applying CFRP sheets as externally bonded strips for flexural strengthening of RC structural elements uses only 20-30% of their strength (Motavalli et al 2011).…”
Section: Introductionmentioning
confidence: 99%